Drug Infusions by Model Predictive Control using Computational Therapeutic Models - Chandramouli, R. (Asian Journal of Pharmaceutics (AJP), 2018)
Intravenous infusion of drugs is preferred choice of drug delivery to critical care patients. However, the conditions of the patients treated require meticulous manual monitoring and control of the drugs infused which is imprecise and guesses prone. Development of adaptive control drug delivery systems to control infusion based on real-time variables will be advantageous in overcoming the stated difficulties, affording the caregiver to dynamically modify the amount of drug infused based on the real-time inputs. Predictive control modeling is a platform for implementing infusion control of hard to infuse drugs with better therapeutic efficiency.